Design of marine macroalgae photobioreactor integrated into building to support seagriculture for biorefinery and bioeconomy. (October 2017) - Chemodanov, Alexander; Robin, Arthur; Golberg, Alexander
Graphical abstract: Highlights: Indoors macroalgae photobioreactor (MPBR) was developed. MPBR integrated in LEED building. Macroalgae ash, energy density, carbohydrates and protein content was measured. Macroalgae accumulated energy was calculated. Abstract: Seagriculture, which can provide offshore grown macroalgae biomass would play a significant role in bioeconomy. Nevertheless, seagriculture development has been hindered by the lack of laboratory photobioreactors that enable fundamental and pilot scale macroalgae research. In this work, a macroalgae photobioreactor (MPBR) was developed and integrated into the building. The MPBR operation was demonstrated for 6 months with cultivation of Cladophora sp., Ulva compressa and Ulva rigida green macroalgae species isolated from 3 sites at the Eastern Mediterranean coast. The growth rate, protein, ash, specific energy density, rhamnose, xylose, arabinose, glucose, galactose and glucuronic acid content of the cultivated species were quantified. The maximum accumulated energy rates were 0.033 Wh L −1  d −1 for Cladophora sp., 0.081 Wh L −1  d −1 for U. compressa and 0.029 Wh L −1  d −1 for U. rigida . This work provides a detailed design of an indoor, urban photobioreactor for cultivation, maintenance and energy balance analysis of macroalgae biomass for biorefinery.